2014
DOI: 10.1111/ruso.12060
|View full text |Cite
|
Sign up to set email alerts
|

Standards for Development: Food Safety and Sustainability in Wal‐Mart's Honduran Produce Supply Chains

Abstract: Public-private partnerships between supermarket retailers and development agencies help small-scale producers reach growing domestic markets in developing countries. Drawing on qualitative data that focuses on relationships between producers, development agencies, and Wal-Martowned supermarkets in Honduras, the research presented here demonstrates how, by introducing food safety standards to development agencies' outreach efforts, but without necessarily certifying producers or offering a price premium, Wal-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 75 publications
(238 reference statements)
2
21
0
Order By: Relevance
“…Fourth, the regulatory framework tends to be more operationally-focused and weak in terms of promoting environmental sustainability (Mitra and Datta, 2014). In the case of the food industry, for instance, the relationship between food safety standards and sustainability requires better specification around which measures to include and exclude from national regulations and how to make both policies compatible (Bloom, 2015).…”
Section: Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, the regulatory framework tends to be more operationally-focused and weak in terms of promoting environmental sustainability (Mitra and Datta, 2014). In the case of the food industry, for instance, the relationship between food safety standards and sustainability requires better specification around which measures to include and exclude from national regulations and how to make both policies compatible (Bloom, 2015).…”
Section: Barriersmentioning
confidence: 99%
“…When talking about assessment, it is found that the purpose of some certifications is to standardize products and processes, thereby creating mass markets and price-based competition. Other standards aim to differentiate the products, thus establishing niche markets based on quality as a form of non-price competition (Bloom, 2015;Dolan, 2008;Vermeulen and Metselaar, 2015). In developing countries, voluntary sustainability standards primarily reach the export-oriented sectors.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forms of marketing support could be locating merchandising officers and providing support for promotion costs. Furthermore studies show that through support from retailers to small-scale suppliers of fresh vegetables were able to supply modern food retailing (Andersson et al, 2015;Bloom, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In order to ensure that the value chain opportunities being developed are pro‐poor, the private sector, state, and civil society often come together in what are called hybrid governance schemes so that, at least ostensibly, power is diffused from the concentrated control of private actors (Bäckstrand ). Often called multistakeholder partnerships, these collaborations typically pursue environmentally or socially responsible third‐party certification schemes (Bloom ; Constance and Bonnano ). Participation in pro‐poor value chains is often an opportunity for agrifood firms to build their portfolios of corporate social responsibility, which seeks to address consumers’ concerns about externalities of market behavior while maintaining competitiveness (Gond, Kang, and Moon, ; Tallontire ).…”
Section: Value Chain Developmentmentioning
confidence: 99%